Training Learning Model PjBL Based on Science Practicum Tools at the Attohiriyah Alfadiliyah Islamic Boarding School, Bodak, Central Lombok - Aris Doyan; Susilawati Susilawati; Yayuk Handayani; Muntari Muntari; Syamsul Hakim; Baiq Hurun Infarlina; Sahwi Sahwi (Pascasarjana Universitas Mataram, 2023)
Community service activities are one of the lecturer's obligations as stated in the tridharma of higher education. The community partner chosen by this service team is the Attohiriyah Bodak High School teacher. This activity is carried out in three stages, namely preparation, implementation and evaluation. The preparation stage was carried out to observe the problems faced by teachers at Attohiriyah Bodak High School, especially the problem of implementing learning and identifying the most effective problem solutions for solving problems. The problem that is resolved is the problem of less varied learning by providing training to teachers to carry out learning using the PjBL model. In the implementation phase, direct training was carried out in the application of the teaching aids-based PjBL learning model. The final stage carried out is the evaluation stage which aims to reflect on the service activities that have been carried out. This evaluation stage is in the form of the teacher's response after the service activity has been carried out, namely that the teacher is very enthusiastic about participating in this activity from start to finish.